PEMBERIAN PUPUK ORGANIK DAN PUPUK ANORGANIK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis) DI PEMBIBITAN - Yulistiati Nengsih (Universitas Batanghari Jambi, 2015)
Relying on amount inorganic fertilizer in a last period on agricultural farming had given amount of disadvantage impacts for our environment and living thing. Organic farming system which is emphasis on a natural farming system that minimize the inorganic fertilizer usenessis one of the way in order to against these impacts. Applying an organic fertilizer is a good way alternative to replace inorganic fertilizer. This research had been held on March to September 2015 in Arang-arang Village, KumpehUlu Sub-district, Muaro Jambi District .The completely randomized factorial design was used with two kinds of treatment. The first treatment was two kinds of growing media (M1: Soil+compost TKKS (2:1) and M2: Soil+compost TKKS (1:2)). While the second treatment was four different levels of inorganic fertilizer e.g. NPK (Po: control; P1: 7,5 g; P2: 15 g and P3: 22,5 g). There are eight kind combinations between the two treatment above e.g. M1Po, M1P1, M1P2, M1P3, M2Po, M2P1, M2P2, and M2P3. There are there time repetitions on each combination, so it had 24 block combinations. Beside there are there plants in each block, then it had been took two plants from each block as a sample.The result of this research showed that the combinations between growing media and inorganic fertilizer (NPK) had significant interaction on Plant height of oil palm plant. However NPK as an individual application showed no significant effect on it plant height. Keywords: Growing media, NPK fertilizer, TKKS